INNOVATION IN THE USE OF FUEL AND ENERGY RESOURCES OF THE COUNTRY - A.T. Djumabekova; R.K. Sabirovа; D.T. Bizhanov; B.M. Bayadilova; Zh.M. Omarkhanova (Academic Journal of Physical and Chemical Sciences, 2019)
The issues of the current state, the problems of prospects for the development of the fuel and energy complex of the Russian Federation. in particular the oil and gas industry. The factors that determine the need for innovative development of the branches of the fuel and energy complex are analyzed. The use of high-tech services in the fuel and energy sector is proposed as a basic element of this development. The authors emphasized the need to increase energy efficiency and reduce the energy intensity of the economy to the level of developed countries and consistently limit the load of the fuel and energy complex on the environment and climate by reducing pollutant emissions, discharging polluted wastewater, as well as greenhouse gas emissions, reducing waste production and energy consumption. Also, promising ways of innovative development of the fuel and energy complexes of Kazakhstan were proposed.